A method for studying the stability of the interface between rock minerals and cement based on molecular simulation
Through molecular dynamics simulation, the method of studying the interface between rock minerals and cement cement is solved, and the problem of the existing technology is difficult to study the interface stability of a single mineral and cement cement in depth, and the micro-level stability investigation and mechanism reveal of the cement interface between different rocks and cement cement is achieved, providing specific measures to improve interface stability.
Patent Information
- Application Number
- CN202510058443.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-15
AI Technical Summary
The prior art is difficult to study the stability of the interface between a single mineral and cement cement in rock components in an in-depth manner, which limits a comprehensive understanding and accurate prediction of the interface stability of different rocks and cement cement.
The molecular dynamics simulation method is used to construct the interface model of rock minerals and cement cement. Through energy minimization and equilibrium simulation, the interface stability and its mechanism are revealed, and the microstructure and interface binding energy of the interface are analyzed through the calculation of stress during uniaxial tensile failure.
The micro-level stability investigation of the interface between different rock minerals and cement cement was realized, revealing the interface stability mechanism, and providing specific measures to improve the weak stability interface. It is simple to operate and strongly promoted, making up for the shortcomings of experimental research.
Smart Images

Figure CN119470040B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oil and gas cementing, and in particular to a method for studying the stability of the interface between rock minerals and cementing cement based on molecular simulation. Background Art
[0002] Cementing is an important part of oil and gas production, and the quality of cementing is directly related to the production capacity and service life of oil and gas wells. The second interface of cementing, that is, the bonding interface between formation rock and cementing cement ring, is the weakest point in the cementing system. The instability of this interface may lead to the failure of the cementing sealing system, causing the leakage of fluids such as oil, gas, and water, and then cause safety accidents such as blowouts, seriously affecting the long-term safety and economic benefits of oil and gas wells. Therefore, in-depth research on the bonding interface between formation rock and cementing cement ring is of great significance to improving cementing quality and ensuring the long-term safe production of oil and gas wells.
[0003] Experiments focus on examining the effects of factors such as rock type and rock interface roughness on the stability of the interface between rock and cementing cement. However, due to the limitations of existing experimental techniques, it is difficult to conduct in-depth research on the stability of the interface between a single mineral in the rock component and cementing cement. This limits the comprehensive understanding and accurate prediction of the stability of the bonding interface between different rocks and cementing cement. Clarifying the stability and mechanism of the bonding interface between different minerals and cementing cement is the key to understanding and predicting the stability of the interface between different types of rocks and cementing cement. Therefore, a new technical method is urgently needed for the study of the stability of the interface between a single mineral and cementing cement.
[0004] Recently, with the rapid development of computing technology and the continuous improvement of computer computing power, molecular dynamics simulation has become an important research method. Molecular dynamics is a theoretical calculation method based on the calculation of the interaction between molecules and atoms to describe the dynamic change process of particles. It has been widely used in the study of nanoscale mechanics. Introducing molecular dynamics into the study of interfaces is expected to reveal the stability of interfaces and their mechanisms at the microscopic level. Summary of the invention
[0005] In view of this, the present invention aims to propose a method for studying the stability of the interface between rock minerals and cementing cement based on molecular simulation. By adopting the molecular dynamics simulation method, a model of the interface between rock minerals and cementing cement is constructed, the stability of the interface between different rock minerals and cementing cement is clarified, and its stability mechanism is revealed.
[0006] To achieve the above object, the technical solution of the present invention is achieved as follows:
[0007] A method for studying the stability of the interface between rock minerals and cementing cement based on molecular simulation, the method comprising the following steps:
[0008] S1. Build the model:
[0009] Use Materials Studio software to construct mineral surface model and cementing cement interface model, and stack the mineral surface model and cementing cement interface model;
[0010] S2. Equilibrium molecular dynamics simulation:
[0011] The system obtained in step S1 is energy minimized using LAMMPS software. After energy minimization is completed, the system is subjected to equilibrium simulation under an isothermal and isobaric ensemble to obtain a fully relaxed interface bonding model.
[0012] S3. Controlled molecular dynamics simulation:
[0013] The atoms at the bottom of the mineral occupying 2 / 3 of the thickness of the mineral surface model are fixed, and the silicate chain of the first layer at the top of the cementing interface is set as a rigid body, and the interface model is destroyed by a uniaxial stretching method that moves the rigid body at a constant speed along the expansion direction of the vacuum layer;
[0014] S4. Calculation of stress during the destruction process:
[0015] During step S3, the stress is calculated, and the stress calculation formula is:
[0016] ;
[0017] F is the magnitude of the external force on the rigid body moving at a constant speed, σ is the tensile stress borne during the interface failure process, and A is the contact area between the rock mineral and the cementing cement interface;
[0018] S5. Analysis of microstructure and interface binding energy:
[0019] The radial distribution function is used to investigate the interface between rock minerals and cement and the microstructure inside cement, and the interfacial binding energy between rock minerals and cement is calculated. The stability mechanism of the interface is revealed from the perspective of structure and energy. At the same time, the interface stability is evaluated based on the interface failure mode and the change of stress during the failure process.
[0020] Furthermore, the mineral is a silicate mineral, specifically any one of quartz, albite, kaolinite or illite.
[0021] Furthermore, the cement interface model is a CSH gel surface model.
[0022] Furthermore, the specific method of constructing the CSH gel surface model is to first remove the water molecules in the Tobermorite crystal, and then randomly delete the [SiO4] 4- tetrahedron, making its Q nThe ratios are close to Q0≈10%, Q1≈67%, and Q2≈23%. Then, a grand canonical Monte Carlo simulation is performed on the model, and water molecules are randomly inserted to finally obtain a water-saturated CSH gel surface model. Finally, the (004) crystal plane of the CSH gel surface model is exposed and used as the cement stone surface model for cementing.
[0023] Furthermore, the distance between the mineral surface model and the cement interface model of the stacked combination is 2-3Å, and a vacuum layer of 40-60Å is reserved above the cement interface model.
[0024] Furthermore, in step S2, the CLAYFF force field is used for both the mineral surface model and the cement interface model, and the system energy is minimized using the steepest descent and conjugate gradient algorithms. The convergence criterion for energy optimization is that the maximum atomic force is less than 50 kJ×mol -1 ×nm -1 ; Equilibrium simulation for 3-5ns under isothermal and isobaric ensemble.
[0025] Further, in step S3, the rigid body was moved at a constant speed of 0.01-0.1Å / ps, and the stretching simulation lasted for 3ns, during which the stress and displacement were recorded every 2ps.
[0026] Furthermore, the interface failure modes include bonding failure mode and cohesive failure mode; in the bonding failure mode, the interface failure occurs at the cementing interface and the rock mineral bonding interface, and the smaller the tensile stress that can be sustained during the failure process, the worse the stability of the interface; in the cohesive failure mode, the failure occurs inside the cementing cement, and the greater the tensile stress that can be sustained during the failure process, the better the stability of the interface.
[0027] In order to deeply explore the stability mechanism of the rock mineral-cementing cement interface, the present invention firstly examines the microstructure of the rock mineral-cementing cement bonding interface and the inside of the cementing cement in the equilibrium state, and then examines the interfacial binding energy of the rock mineral and the cementing cement. From the perspective of the interface microstructure and the interface binding energy, the stability mechanism of the rock mineral-cementing cement interface is revealed.
[0028] Compared with the prior art, the method for studying the stability of the interface between rock minerals and cementing cement based on molecular simulation described in the present invention has the following advantages:
[0029] The present invention provides a simple and effective method for analyzing the stability of rock mineral-cement interface, which can realize the investigation of the stability of different rock minerals and cementing cement interfaces at the microscopic level, especially the investigation of the stability mechanism of different rock minerals and cementing cement at the microscopic level, so as to propose specific improvement measures at the molecular level for weak stability interfaces. The method is simple to operate and has strong applicability, which makes up for the shortcomings of cumbersome operation, long cycle and high cost in experimental research. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0031] Figure 1 is the interface model constructed in Example 1; wherein (a) is the CSH gel surface model; (b) is the SiO2 surface model; (c) is the SiO2 and CSH gel interface model;
[0032] Figure 2 This is the uniaxial stretching method adopted in Example 1 to destroy the interface model of SiO2 and CSH gel;
[0033] Figure 3 1 is a diagram of the uniaxial tensile failure process of the SiO2 and CSH gel interface model in Example 1; wherein (a) is the initial state of the model, (b)-(f) are the changing states of the model during the failure, and (g) is the end state of the tensile failure;
[0034] Figure 4 is the stress change of the SiO2 and CSH gel interface model during uniaxial tension in Example 1;
[0035] Figure 5 is the radial distribution function between the corresponding atoms at the interface of SiO2 and CSH gel in Example 1; Cah represents the Ca ions in the CSH interlayer region or on the CSH surface, Oh and Ho represent the hydroxyl O atoms and H atoms on the SiO2 surface, respectively, and Onb represents the non-bridging oxygen atoms of the silicate chain on the CSH surface;
[0036] Figure 6 The microstructures at the interface of SiO2 and CSH gel in Example 1, wherein (a) is a microstructure diagram of the interface Ca ions acting as bridges at the interface, and (b) is a microstructure diagram of the hydrogen bonds formed between the silicate chains on the CSH surface and the SiO2 surface;
[0037] Figure 7is the radial distribution function between the corresponding atoms in each region inside the CSH in Example 1; Cah represents the Ca ions in the CSH interlayer region or the CSH surface, Cao represents the Ca ions in the intralayer (Ca-O layer) region, Ow and Hw represent the oxygen atoms and hydrogen atoms in the water molecules, respectively, Oh and Ho represent the hydroxyl O atoms and H atoms on the SiO2 surface, respectively, and Onb represents the non-bridging oxygen atoms of the silicate chain on the CSH surface;
[0038] Figure 8 is a schematic diagram of the microstructure of each region inside the CSH gel in Example 1;
[0039] Fig. 9 is the interfacial binding energy between CSH and SiO2 and Iliite and the cohesive energy of CSH in Examples 1 and 2;
[0040] Fig.10 1 is a diagram of the uniaxial tensile failure process of the interface model of Iliite and CSH gel in Example 2; wherein (a) is the initial state of the model, (b)-(f) are the changing states of the model during the failure, and (g) is the end state of the tensile failure;
[0041] Fig.11 is the stress change of the interface model of Illite and CSH gel during uniaxial stretching in Example 2;
[0042] Fig.12 is the radial distribution function between the atomic pairs that are most likely to have stable interactions at the interface between Illite and CSH gel in Example 2; Cah represents the Ca ions on the CSH surface, and Ob represents the bridging oxygen atoms on the Illite surface;
[0043] Fig.13 This is the microstructure at the interface of Illite and CSH gel in Example 2; Cah represents the Ca ions on the CSH surface, and Ob represents the bridging oxygen atoms on the Illite surface. DETAILED DESCRIPTION
[0044] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.
[0045] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0046] The computer simulation software used in the method of the present invention is Materials Studio (MS), a new generation of material calculation software developed by Accelrys Corporation of the United States, and LAMMPS (Large-scale Atomic / Molecular Massively Parallel Simulator), an open source program package for molecular dynamics simulation developed by Sandia National Laboratories.
[0047] The main contents of the present invention include two parts: first, constructing an interface model formed by rock minerals and cementing cement; second, investigating the stability of the interface by uniaxial tensile failure of the interface model. This study reveals the interface stability and mechanism of rock mineral-cementing cement at the microscopic level.
[0048] Example 1 Simulation of interface stability between quartz (SiO2) and cement
[0049] The steps include:
[0050] S1. Build the model:
[0051] Mineral surface model:
[0052] The SiO2 surface model was obtained by cutting α-cristobalite along the (001) crystal plane and hydroxylating the exposed surface.
[0053] Cement interface model:
[0054] The CSH gel surface model was constructed according to the method proposed by Pellenq et al.: first, water molecules were removed according to the Tobermorite crystal model proposed by Hamid, and then [SiO4] on the silicate chain of the Tobermorite crystal was randomly deleted. 4- tetrahedron, making its Q n The ratios are close to Q0≈10%, Q1≈67%, and Q2≈23%. Then, a grand canonical Monte Carlo simulation was performed on this model, water molecules were randomly inserted, and a water-saturated CSH gel surface model was obtained, and its (004) crystal plane was exposed as the cementing cement surface.
[0055] The obtained SiO2 surface model was superimposed and spliced with the CSH gel surface model. The CSH gel surface model was placed about 2Å above the SiO2 surface model, and a 50Å vacuum layer was reserved above it, thereby forming an interface model of SiO2 and CSH gel. The interface model is shown in Figure 1 shown.
[0056] S2. Equilibrium molecular dynamics simulation (EMD):
[0057] The system was simulated by equilibrium molecular dynamics (EMD) using LAMMPS software. The SiO2 and CSH gel surface models were both simulated using the CLAYFF force field. First, the system was energy minimized using the Steepest Descent and Conjugate Gradient algorithms, respectively. The convergence criterion for energy optimization was that the maximum atomic force was less than 50 kJ×mol -1 ×nm -1 After completing the energy minimization, a 5 ns equilibrium MD simulation was performed on the system under the isothermal and isobaric (NPT) ensemble to fully relax the system. The temperature was set to 300 K and the time step was 1 fs. In addition, the Nose-Hoover thermal bath algorithm was used for temperature control throughout the simulation.
[0058] The simulation box adopts three-dimensional periodic boundary conditions, the neighbor list and the cutoff radius of van der Waals and electrostatic interactions are uniformly set to 1.2nm, and the long-range electrostatic interactions are calculated by the Particle Mesh Ewald (PME) method.
[0059] S3, controlled molecular dynamics simulation (SMD):
[0060] Afterwards, EMD relaxation was continued for 3 ns in the isothermal and isobaric (NVT) ensemble state, and then the atoms of 6 Å thickness at the bottom of SiO2 were fixed, and the silicate chain of the first layer on the top of CSH was set as a rigid body, and relaxation was performed for 5 ns in the NVT ensemble state for internal stress pre-relaxation.
[0061] Then, a controlled molecular dynamics simulation was performed on the interface model, in which the top part of the CSH was set as a rigid body and moved at a constant speed V = 0.01Å / ps along the Z direction (the direction in which the vacuum layer expanded), while keeping the atoms at the bottom of SiO2 fixed. The stretching simulation lasted for 3ns, during which the stress and displacement were recorded every 2ps.
[0062] S4. Calculation of stress during the destruction process:
[0063] During the process of step S3, the magnitude of the external force F generated on the rigid body moving at a constant speed due to deformation and destruction of the interface model is recorded, and the tensile stress borne by the interface model is calculated using the following formula:
[0064] ;
[0065] σ is the tensile stress borne by the interface during the destruction process, A is the contact area between CSH and rock minerals, such as Figure 2 Controlled molecular dynamics simulation of uniaxial stretching shown.
[0066] S5. Analysis of microstructure and interface binding energy:
[0067] The interface stability of the interface model can be evaluated by combining the failure mode of the interface model and the change of stress during the failure process. If the interface failure occurs at the cementing interface between CSH gel and rock minerals (adhesive failure mode), and the smaller the tensile stress that can be sustained during the failure process, the worse the stability of the interface. On the contrary, if the failure occurs inside the CSH (cohesive failure mode), and the larger the tensile stress that can be sustained during the failure process, the better the stability of the interface.
[0068] Figure 3 : is a diagram of the uniaxial tensile failure process of the SiO2 and CSH gel interface model in this embodiment. It can be seen from the figure that after uniaxial tensile failure, the interface failure occurs inside the CSH, and a cohesive failure mode occurs. The interface can withstand a high stress of about 1.75 GPa (e.g., Figure 4 ), indicating that the interface has good stability.
[0069] Combined with the stress change during the failure process ( Figure 4 ), the failure process can be divided into four stages, namely, I elastic deformation stage, II plastic deformation stage, III fracture stage, and IV residual stress stage. The changes in interface configuration corresponding to each stage are shown in Figure 3 As shown in the figure, after undergoing typical elastic deformation, the interface system undergoes plastic deformation. At the end of the plastic deformation, microcracks are generated in the interlayer position containing water inside the CSH. As the deformation continues to increase, the cracks continue to expand in the interlayer region until they penetrate the entire interlayer region. The crack expansion process corresponds to the fracture stage in the stress change process. After the crack penetrates, some atomic chains still bridge the fracture area, corresponding to the residual stress stage.
[0070] The radial distribution function is further combined to analyze the microstructure of the interface between SiO2 and CSH gel and the internal regions of CSH, such as Figure 5-8 shown.
[0071] like Figure 5-6 As shown in the figure, there are hydrogen bonds and Ca-O coordination interactions on the cementing interface. The Ca ions on the interface can also coordinate with the non-bridging oxygen atoms (Onb) of the silicate chain on the CSH surface and the hydroxyl oxygen (Oh) on the SiO2 surface, thus playing a bridging role. It can be seen that the hydrogen bonds on the interface and the bridging effect of calcium ions maintain the stability of the interface cementation. Figure 7-8As shown in the figure, CSH has an obvious layered structure, which is divided into the Ca-O layer region and the water-containing interlayer region. The radial distribution function analysis shows that there is a strong coordination interaction between the calcium ions (Cao) in the Ca-O layer and the non-bridging oxygen atoms (Onb) on the silicate chain. It is this interaction that maintains the mechanical stability of this region. There are multiple interactions in the water-containing interlayer region, including hydrogen bonding between water molecules, hydrogen bonding between water molecules and non-bridging oxygen atoms (Onb) on silicates, coordination interactions between water molecules and calcium ions (Cah) in the interlayer region, and coordination interactions between calcium ions (Cah) and non-bridging oxygen atoms (Onb). It is these interactions that together maintain the mechanical stability of this region. As can be seen from the fact that the fracture occurs in this region, the synergy of multiple interactions does not enhance the mechanical stability of this region, but instead makes this region a mechanically weak region in CSH.
[0072] The interfacial binding energy between SiO2 and CSH and the cohesive energy of CSH are further calculated, as Fig. 9 As shown in the figure, the interfacial binding energy between SiO2 and CSH is greater than the cohesive energy of CSH, which is also the key reason why the fracture occurs inside CSH rather than at the bonding interface.
[0073] Based on the above results, it can be seen that it is the hydrogen bonds at the interface and the bridging effect of calcium ions at the interface that enable the SiO2 and CSH cementing interface to maintain good bonding stability, while the interlayer region containing water inside CSH has weak mechanical properties and is the key area to improve the overall stability of the SiO2 and CSH cementing interface.
[0074] Example 2 Simulation of the stability of the interface between illite and cement
[0075] The steps include:
[0076] S1. Build the model:
[0077] Mineral surface model:
[0078] The Illite surface model was obtained by exposing the (001) crystal plane of the Illite crystal.
[0079] It should be noted that the construction of the mineral surface model is based on the cleavage plane of the mineral. The hydroxylation treatment of the SiO2 surface is mainly based on the actual situation that the rock wall is in a wet environment during the cementing process and there are a large number of active suspended O atoms on the exposed surface of SiO2; the exposed surface of Illite is a stable bridging oxygen atom surface, which can exist stably in a wet environment, so it does not need to be hydroxylated.
[0080] Cement interface model:
[0081] The construction method is the same as in Example 1.
[0082] Similarly, the obtained Illite surface model was superimposed and spliced with the CSH gel surface model. The CSH gel surface model was placed about 2Å above the Illite surface model, and a 50Å vacuum layer was reserved above it, thus forming the Illite and CSH gel interface model.
[0083] The simulation method of S2 and S3 is the same as that of Example 1.
[0084] During step S3, the stress is calculated and the stress change is recorded.
[0085] Fig.10 is a diagram of the uniaxial tensile failure process of the Illite and CSH gel interface model in this embodiment, combined with the stress change during the failure process ( Fig.11 ), the failure process can be divided into three stages, I represents the elastic deformation stage, II represents the failure stage corresponding to the stress drop, and III represents the complete failure stage. As can be seen from the figure, after uniaxial tensile failure, the fracture process is relatively simple, and complete fracture occurs after a small deformation. Interface failure occurs at the CSH and Illite interface, and a bonding failure mode occurs. The maximum failure stress of the interface before reaching the final failure is small, about 0.75GPa (such as Fig.11 ), indicating that the stability of the interface is poor.
[0086] The microstructure of the interface between Illite and CSH was investigated by combining the radial distribution function, and it was found that no stable bonding structure was formed on the interface (such as Fig.12 and Fig.13 ), which leads to weak bonding between Illite and CSH. The calculation of its interface binding energy also supports this view, such as Fig. 9 As shown in the figure, the interface binding energy of CSH and Illite is much lower than the cohesive energy of CSH. It can be seen that the weak bonding at the interface between Illite and CSH directly causes the poor stability of the interface. Therefore, improving the weak bonding at the interface between Illite and CSH is the key to improving its interface stability.
[0087] In summary, the method of the present invention can be used to investigate the stability of the bonding interface between different rock minerals and cementing cement at the microscopic level, especially to investigate the stability mechanism of different rock minerals and cementing cement at the microscopic level, so that specific improvement measures can be proposed at the molecular level for weak stability interfaces. The method is simple to operate and has strong scalability, which makes up for the shortcomings of cumbersome operation, long cycle and high cost in experimental research.
[0088] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for studying the stability of the interface between rock minerals and cement based on molecular simulation, characterized in that: The method comprises the following steps: S1. Build the model: Use Materials Studio software to construct silicate mineral surface model and cementing cement interface model CSH gel model, and stack the mineral surface model and cementing cement interface model. The distance between the mineral surface model and the cementing cement interface model is 2-3Å, and a 40-60Å vacuum layer is reserved above the cementing cement interface model. S2. Equilibrium molecular dynamics simulation: The system obtained in step S1 is energy minimized using LAMMPS software. After energy minimization is completed, the system is subjected to equilibrium simulation under an isothermal and isobaric ensemble to obtain a fully relaxed interface bonding model. S3. Controlled molecular dynamics simulation: The atoms at the bottom of the mineral occupying 2 / 3 of the thickness of the mineral surface model are fixed, and the silicate chain of the first layer on the top of the cementing interface is set as a rigid body, and the interface model is destroyed by the uniaxial stretching method that moves the rigid body along the expansion direction of the vacuum layer at a constant speed of 0.01-0.1Å / ps; the stretching simulation lasts for 3ns, during which the stress and displacement are recorded every 2ps; S4. Calculation of stress during the destruction process: During step S3, the stress is calculated, and the stress calculation formula is: ; F is the magnitude of the external force on the rigid body moving at a constant speed, σ is the tensile stress borne during the interface failure process, and A is the contact area between the rock mineral and the cementing cement interface; S5. Analysis of microstructure and interface binding energy: The radial distribution function is used to investigate the interface between rock minerals and cement and the microstructure inside cement, and the interfacial binding energy between rock minerals and cement is calculated. The stability mechanism of the interface is revealed from the perspective of structure and energy. At the same time, the interface stability is evaluated by combining the interface failure mode and the change of stress during the failure process. The interface failure modes include bonding failure mode and cohesive failure mode; in the bonding failure mode, the interface failure occurs at the cementing interface between the cementing interface and the rock mineral surface, and the smaller the tensile stress that can be sustained during the failure process, the worse the stability of the interface; in the cohesive failure mode, the failure occurs inside the cementing cement, and the greater the tensile stress that can be sustained during the failure process, the better the stability of the interface.
2. The method for studying the stability of the interface between rock minerals and cement based on molecular simulation according to claim 1, characterized in that: Specifically, it is any one of quartz, albite, kaolinite or illite.
3. The method for studying the stability of the interface between rock minerals and cement based on molecular simulation according to claim 1, characterized in that: The specific construction method of the CSH gel surface model is: first remove the water molecules in the Tobermorite crystal, and then randomly delete the [SiO4] 4- tetrahedron, making its Q n The ratios are close to Q0≈10%, Q1≈67%, and Q2≈23%. Then, a grand canonical Monte Carlo simulation is performed on the model, and water molecules are randomly inserted to finally obtain a water-saturated CSH gel surface model. Finally, the (004) crystal plane of the CSH gel surface model is exposed and used as the cement stone surface model for cementing.
4. The method for studying the stability of the interface between rock minerals and cement based on molecular simulation according to claim 1, characterized in that: In step S2, the CLAYFF force field is used for both the mineral surface model and the cement interface model, and the system energy is minimized using the steepest descent and conjugate gradient algorithms. The convergence criterion for energy optimization is that the maximum atomic force is less than 50 kJ×mol -1 ×nm -1 ; Equilibrium simulation for 3-5ns under isothermal and isobaric ensemble.